2007
DOI: 10.1152/ajpheart.00826.2007
|View full text |Cite
|
Sign up to set email alerts
|

Beneficial effect of heme oxygenase-1 expression on myocardial ischemia-reperfusion involves an increase in adiponectin in mildly diabetic rats

Abstract: Transient reduction in coronary perfusion pressure in the isolated mouse heart increases microvascular resistance (paradoxical vasoconstriction) by an endothelium-mediated mechanism. To assess the presence and extent of paradoxical vasoconstriction in hearts from normal and diabetic rats and to determine whether increased heme oxygenase (HO)-1 expression and HO activity, using cobalt protoporphyrin (CoPP), attenuates coronary microvascular response, male Wistar rats were rendered diabetic with nicotinamide/str… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

10
103
0

Year Published

2008
2008
2011
2011

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 92 publications
(113 citation statements)
references
References 66 publications
10
103
0
Order By: Relevance
“…This would confirm the report of Wang et al (47) that showed that the chaperone protein EroL increased adiponectin. We also have previously shown that upregulation of HO-1 protein in diabetic rats provided both cardio-protection and vascular protection against ROS (24).…”
Section: Decreasing Omentioning
confidence: 74%
See 2 more Smart Citations
“…This would confirm the report of Wang et al (47) that showed that the chaperone protein EroL increased adiponectin. We also have previously shown that upregulation of HO-1 protein in diabetic rats provided both cardio-protection and vascular protection against ROS (24).…”
Section: Decreasing Omentioning
confidence: 74%
“…Ϫ production (23,24). PPAR␥ agonists are shown to induce both HO-1 (21) and the rate-limiting chaperone protein EroL (46,47).…”
Section: Decreasing Omentioning
confidence: 99%
See 1 more Smart Citation
“…We first examined whether cilostazol induced HO-1 expression in VSMC, because HO-1 increases the intracellular cAMP levels [20]. HO-1 expression is associated with increases in adiponectin and AMPK activation [21,22]. Our results indicated that cilostazol increased HO-1 and p-AMPK expression with dose-and time-dependent manners (Fig.…”
Section: Discussionmentioning
confidence: 97%
“…However, these findings do not necessarily implicate bilirubin as the protective agent given that they are based solely on association studies. Finally, the administration of bilirubin or its precursor biliverdin to rodents can suppress unwanted reactions such as ischemia/reperfusion injury (23,28) and allograft rejection (23,29). However, up until now, few studies have addressed the issue of the role of biliverdin/bilirubin in the prevention of microvascular structural alterations, and in the development of organ damage in hypertension.…”
Section: Discussionmentioning
confidence: 99%